THE ROLE OF WRITING SKILL AS AN ALTERNATIVE MEDIA OF CHARACTER FORMATION - Zuhdy, Halimi; Ulya, Muflikhah (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media), 2021)
Recently, character education has become the cynosure both in society and educational institutions. In addition, discussions about character have been studied widely in scientific meeting forums. However, life problems that are often present in today's society are very complex. These problems happen due to the low and lack of character education in families, communities, and educational institutions. Therefore, to solve this problem, writing skills are present as an alternative media for character building. Honing writing skills by making habituation and maximizing its implementation function will impact the formation of being honest, responsible, confident, polite, hard-working, creative, innovative, critical, and analytical characters. This study aims to identify the role of writing skills as an alternative media for character formation. This research is library research using a qualitative method approach. The finding shows that honing writing skills can be an alternative tool for character building by internalizing certain traits and values reflected in thoughts, emotions, and behavior.